The development of Pomacea maculata fed on Oryza sativa and Limnocharis flava - Shahidan, Nurul Fatini (2017)
Pomacea maculata is a serious pest of paddy in Asia, especially Southeast Asia where Malaysian paddy fields are reported to be particularly highly infested by Pomacea spp. Recently, P. maculata was discovered to prefer consuming Limnocharis flava, a common weed in paddy field raising speculation of its potential use as a trap crop to reduce the damages by P. maculata on paddy seedlings. Subsequent to that, an experiment was conducted in the Glasshouse Unit at Ladang 2 and also at the Insects Ecology Laboratory, Department of Plant Protection, Faculty of Agriculture, Universiti Putra Malaysia to study the effect of Oryza sativa and L. flava as food sources on the growth and development of P. maculata. Eighty (80) hatchlings of same ages were equally divided into two groups based on their rearing diets, which were either fresh three (3) weeks old rice seedlings or L. flava. Each group was fed ad libitum with their respective diet daily. The experiment was laid out in Completely Randomized Design (CRD) with four replications. The growth parameter of Shell Length, Shell Width, Aperture Length, Aperture Width and Spire Height of P. maculata were measured on five randomly selected individuals on weekly basis for two months. Data was analyzed using two sample t-test procedure in SAS. The results show that there is a significant difference (p<0.05) between the treatments for all the parameters starting from week six onwards. During the 12ᵗʰ week, L. flava gave the highest mean shell length (14.52 ± 0.27), shell width (10.62 ± 0.15), aperture length (11.65 ± 0.20), aperture width (8.27 ± 0.18) and spire height (3.11 ± 0.12). Therefore, L. flava is highly recommended to be planted as the trap crop in paddy fields to reduce the damages to paddy plantation by P. maculata. The finding also implies that P. maculata may serve as biological control agent for the invasive L. flava in ecosystems where it is found to be a menace.